Imagined Audiences, Emotions, and Feedback Expectations in Social Media Photo Sharing. (July 2021) - Stsiampkouskaya, Kseniya; Joinson, Adam; Piwek, Lukasz; Stevens, Lorna
The present research explores the effects of imagined audiences, emotions, and feedback expectations on social media photo sharing. We focus on the audience-oriented approach to sharing and on how discrepancies between expected and received feedback might shape photo sharing behaviors. Twenty-four participants were interviewed using scenario-based semi-structured interview method. The participants were asked to develop an imagined story about two fictional individuals who decided to share a photo on their social media. The story was guided by questions about the characters' motivations and incentives to post and explored three alternative scenarios representing the reception of usual feedback, better than usual feedback, and the absence of expected feedback, respectively. The results indicate that individuals often adopt their audience's perspective when choosing a photo to post, and consider whether the chosen image would evoke sufficient interest to induce feedback. The participants believed that emotional photos engaged their audience and motivated the viewers to provide feedback. Furthermore, the study identified and analyzed the concept of feedback expectations. When received feedback exceeded the expectations, individuals experienced happiness. However, the replication of successful content was considered appropriate only if accompanied by a suitable caption and posted after a period of time. When received feedback failed to meet their expectations, individuals felt disconnected from their audiences and experienced disappointment. They employed rationalization and feedback dismissal as coping mechanisms and displayed two common behavioral responses to unsuccessful feedback; they attempted to repost the photo avoiding previous mistakes, and they changed the style of content they posted.